2023
DOI: 10.1136/bmjgh-2022-010370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a mobile app chatbot and an interactive small-group webinar on COVID-19 vaccine intention and confidence in Japan: a randomised controlled trial

Abstract: IntroductionWe investigated the effect of social media-based interventions on COVID-19 vaccine intention (VI) and confidence in Japan.MethodsWe conducted a three-arm randomised controlled trial between 5 November 2021 and 9 January 2022 during a low incidence (<1000/day) of COVID-19 in Japan in the midst of the second and the third waves. Japanese citizens aged ≥20 who had not received any COVID-19 vaccine and did not intend to be vaccinated were randomly assigned to one of the following three groups: (1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(50 reference statements)
0
0
0
Order By: Relevance
“… 9 10 Most studies of the effects of social media on vaccine behaviours and their antecedents are limited to English language media from high income countries. Of the 17 clinical trials published on this topic in the past six years that we identified from PubMed, 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 10 were limited to participants based in the US; of these, only one enrolled participants who were not fluent in English (web appendix). A systematic review of social media’s influence on vaccination against human papillomavirus reported that most studies were conducted in the US (n=11); others were from Canada and South Korea (n=2 each) and from Taiwan, South Africa, Australia, the UK, and Romania (n=1 each).…”
Section: Data Absenteeism Inequalities and Surveillancementioning
confidence: 99%
“… 9 10 Most studies of the effects of social media on vaccine behaviours and their antecedents are limited to English language media from high income countries. Of the 17 clinical trials published on this topic in the past six years that we identified from PubMed, 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 10 were limited to participants based in the US; of these, only one enrolled participants who were not fluent in English (web appendix). A systematic review of social media’s influence on vaccination against human papillomavirus reported that most studies were conducted in the US (n=11); others were from Canada and South Korea (n=2 each) and from Taiwan, South Africa, Australia, the UK, and Romania (n=1 each).…”
Section: Data Absenteeism Inequalities and Surveillancementioning
confidence: 99%